2010
DOI: 10.1007/s00284-010-9797-9
|View full text |Cite
|
Sign up to set email alerts
|

Sequence Analysis of East Asian cagA of Helicobacter pylori Isolated from Asymptomatic Healthy Japanese and Thai Individuals

Abstract: CagA, especially East Asian type, is one of the most important virulence factors of Helicobacter pylori, which is believed to contribute to the gastric cancer development. There is extreme sequence heterogeneity on 3' region of cagA gene, demonstrated by the sequence analysis of cagA of H. pylori strains isolated from gastric disease patients. However, whether such heterogeneity of the cagA gene sequence is related to the pathogenicity of H. pylori in the gastric cancer development is not certain. Therefore, i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 25 publications
0
1
1
Order By: Relevance
“…Discrete genotypes of cag A associate with severity of gastrointestinal diseases 48 . Unclassified type (AB type) represented the major cag A genotype in this study, in contrast with earlier reports indicating that AB represents only a minority genotype carried by otherwise healthy Thais 41 49 . Here, 22% of the cag A-encoded sequences were Western type (ABC type) with no East Asian type (ABD type), lower than reported for liver fluke infection-induced CCA 44 .…”
Section: Discussioncontrasting
confidence: 99%
“…Discrete genotypes of cag A associate with severity of gastrointestinal diseases 48 . Unclassified type (AB type) represented the major cag A genotype in this study, in contrast with earlier reports indicating that AB represents only a minority genotype carried by otherwise healthy Thais 41 49 . Here, 22% of the cag A-encoded sequences were Western type (ABC type) with no East Asian type (ABD type), lower than reported for liver fluke infection-induced CCA 44 .…”
Section: Discussioncontrasting
confidence: 99%
“…Mane et al [12] also studied the cagA gene of a strain isolated from an Amerindian subject and reported that there was a substantial divergence of that Amerindian strain from the Old World strains. Recently Hirai et al [13] studied the cagA 3′ region of isolates from asymptomatic healthy Japanese and Thai subjects and compared with those from patients with GC. They suggested that cagA sequence differences between those subjects might be linked to GC incidence in Japan and Thailand.…”
Section: Introductionmentioning
confidence: 99%